2015
DOI: 10.1186/s12896-015-0129-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, production, purification and characterization of an organic-solvent-thermostable alkalophilic cellulase from Bacillus vallismortis RG-07

Abstract: BackgroundThe rising concerns about the scarcity of fossil fuels, the emission of green house gasses and air pollution by incomplete combustion of fossil fuel have also resulted in an increasing focus on the use of cellulases to perform enzymatic hydrolysis of the lignocellulosic materials for the generation of bioethanol. The aim of this study was to isolate a potential thermo-solvent tolerant cellulase producing bacterium from natural resources, and then applied for purification and characterization. The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
102
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(123 citation statements)
references
References 33 publications
15
102
2
4
Order By: Relevance
“…The key characteristic of cellulase secreted by most Bacillus sp is its activity at broad pH range (Mawadza et al 2000). Slightly similar optimum CMCase activity was found at pH 7 for B. vallismortis RG-07 (Gaur and Tiwari 2015), Bacillus sp. (Sadhu et al 2013).…”
Section: Characterization Of Cellulase Enzyme Effect Of Ph and Tempermentioning
confidence: 73%
“…The key characteristic of cellulase secreted by most Bacillus sp is its activity at broad pH range (Mawadza et al 2000). Slightly similar optimum CMCase activity was found at pH 7 for B. vallismortis RG-07 (Gaur and Tiwari 2015), Bacillus sp. (Sadhu et al 2013).…”
Section: Characterization Of Cellulase Enzyme Effect Of Ph and Tempermentioning
confidence: 73%
“…There are very few studies that have reported on the optimum activity of cellulase by some thermophilic Bacillus species above 50 °C (Rastogi et al 2010;Annamalai et al 2013;Gaur and Tiwari 2015). Of those studies, most of them did not directly deal with enzymatic hydrolysis.…”
Section: Effect Of Hydrolysis Time On Sugar Production and Saccharifimentioning
confidence: 99%
“…Endoglucanases attract a lot of attention and have been widely used in various industrial application such as textile and detergent industry (Gaur and Tiwari, 2015), which maily catalyzes the hydrolysis of the cellulose by breaking the internal bonds of glucose molecules. Recently, neutral Relative pH stability of recombinant EgH31.…”
Section: Discussionmentioning
confidence: 99%
“…The biological deinking treatment can be improved with the properties of recycling fibers from waste paper, such as fiber brightness, strength properties, higher pulp cleanliness, et al (Gübitz et al, 1998;Gaur and Tiwari, 2015).…”
Section: Introductionmentioning
confidence: 99%